Bio-inspired computing : theories and applications : 14th International Conference, BIC-TA 2019, Zhengzhou, China, November 22-25, 2019, Revised selected papers.: theories and applications : 14th International Conference, BIC-TA 2019, Zhengzhou, China, November 22-25, 2019, Revised selected papers. Part II (2020) - Unknown
No abstract available